MORPHOLOGICAL TYPES OR MARINE BENTHOS AND PLANKTONS - RIOJA, ENRIQUE (My University, 1964)
The classifications of Gislen and Rioja are compared and discussed
CIENC MEX
Keywords: MORPHOLOGICAL TYPES, MARINE BENTHOS, PLANKTONS; MULTIDISCIPLINARIA; BIOLOGIA VEGETAL; BIOLOGIA MARINA